Religious Experiences in the Context of Bipolar Disorder: Serious Pathology and/or Genuine Spirituality? A Narrative Review against the Background of the Literature about Bipolar Disorder and Religion - Ouwehand, Eva (Religions, 2024)
Literature about bipolar disorder and religion is scarce and primarily encompasses studies with a quantitative design. Results of such studies do not lead to unambiguous conclusions about the relation between bipolar disorder and religion that could be applied in clinical practice. The main focus of this article will be on the domain of religious experiences/religious delusions and hallucinations as explored in two recent PhD studies regarding mixed methods and qualitative research, conducted in the Netherlands and in Canada. In the narrative review of the two studies, the occurrence of different types of religious experiences and various explanatory models of patients to interpret them are presented. The interpretation of religious experiences, often related to mania, proves to be an intense quest, and often a struggle for many patients, whereby fluctuations in mood, course of the illness, religious or philosophical background, and the reactions of relatives and mental health professionals all play a role. Patients combine various explanatory models, both medical and religious/cultural, to interpret their experiences and these may fluctuate over the years. The two studies are placed in the context of literature about bipolar disorder and various aspects of religion to date. Finally, the challenges for future research and the implications for clinical practice will be outlined.